Oral Reading Assessment: Four Conditions Where Caution Is Warranted - Zipoli, R.P.; Ramachandar, S. (Assessment for Effective Intervention, 2023)
Assessments of oral reading are widely used for screening, progress monitoring, and comprehensive evaluations. Despite the utility and technical adequacy of these tools, there are subgroups of students for whom measures of oral reading may be inappropriate. The first section of this article focuses on how tests of oral reading may underestimate word reading ability and reading fluency among four subgroups of students with speech, language, or learning difficulties. These include school-age students who demonstrate word-finding difficulties (which are common among students with a learning disability or developmental language disorder), developmental stuttering, childhood apraxia of speech, and pediatric dysarthria. The second section offers practical recommendations for more accurate assessment procedures, correct placement decisions, relevant professional learning activities, and strategic interdisciplinary teaming. © Hammill Institute on Disabilities 2023.
Keywords: communication disorders; dept.cmd; learning disability; peer-reviewed; reading/literacy

Predicting speech-in-speech recognition: Short-term audibility and spatial separation - Wasiuk, P.A.; Calandruccio, L.; Oleson, J.J.; Buss, E. (Journal of the Acoustical Society of America, 2023)
Quantifying the factors that predict variability in speech-in-speech recognition represents a fundamental challenge in auditory science. Stimulus factors associated with energetic and informational masking (IM) modulate variability in speech-in-speech recognition, but energetic effects can be difficult to estimate in spectro-temporally dynamic speech maskers. The current experiment characterized the effects of short-term audibility and differences in target and masker location (or perceived location) on the horizontal plane for sentence recognition in two-talker speech. Thirty young adults with normal hearing (NH) participated. Speech reception thresholds and keyword recognition at a fixed signal-to-noise ratio (SNR) were measured in each spatial condition. Short-term audibility for each keyword was quantified using a glimpsing model. Results revealed that speech-in-speech recognition depended on the proportion of audible glimpses available in the target + masker keyword stimulus in each spatial condition, even across stimuli presented at a fixed global SNR. Short-term audibility requirements were greater for colocated than spatially separated speech-in-speech recognition, and keyword recognition improved more rapidly as a function of increases in target audibility with spatial separation. Results indicate that spatial cues enhance glimpsing efficiency in competing speech for young adults with NH and provide a quantitative framework for estimating IM for speech-in-speech recognition in different spatial configurations. © 2023 Acoustical Society of America.
Keywords: dept.cmd; peer-reviewed

Aphasia, alexia, and agraphia - Purdy, Mary H. (Encyclopedia of Mental Health, Third Edition: Volume 1-3, 2023)
Aphasia is a language disorder that occurs as a result of brain damage. It affects auditory comprehension, verbal expression, reading, and writing due to the disruption of specific language components such as phonology, semantics, and/or syntax. A hallmark characteristic of aphasia is anomia, or impaired word retrieval. This may occur in the context of fluent speech (normal rate, rhythm and prosody) or nonfluent speech (hesitant and agrammatic verbal output). Other characteristics of aphasia vary depending on the specific location and extent of brain damage. Alexia and agraphia are acquired impairments in reading and writing, respectively. These deficits may occur in isolation but more commonly co-occur with aphasia. Assessment and treatment of aphasia, alexia, and agraphia focuses on identifying and restoring impaired function as well as determining the impact of the impairment of quality of life and developing compensatory strategies to manage persisting deficits. This article describes the symptoms associated with aphasia, alexia, and agraphia, the subtypes and neurological correlates of each impairment, the general trajectory of recovery, and assessment and treatment approaches. © 2023 Elsevier Inc. All rights reserved.
Keywords: Acquired language disorders; Agraphia; Alexia; Aphasia; Communication disorder; Dysgraphia; Dyslexia; Dysphasia; dept.cmd

Utilization of instrumentation in swallowing assessment of surgical patients during COVID-19 - Warner, Heather; Coutinho, Jennifer M.; Young, Nwanmegha (Life, 2023)
The aim of this study is to describe a measured return to instrumental dysphagia assessments for our vulnerable surgical patient population, such that best practice patterns could be resumed and our staff kept safe from transmission of COVID-19. A retrospective medical record review provided data on clinical practice patterns of swallowing assessment in an at-risk surgical patient population. Outcomes of this study support protocols that allow clinicians to safely resume the use of instrumental assessment and return to best practice in dysphagia assessment for our surgical patient population.
Keywords: COVID-19; Fiberoptic Endoscopic evaluation of swallowing; deglutition; dept.cmd; dysphagia; peer-reviewed; surgical; swallowing assessment

A cross-sectional investigation of disfluencies in typically developing Spanish-English bilingual children - Rojas, Raúl; Irani, Farzan; Gusewski, Svenja; Camacho, Natalia (Journal of Fluency Disorders, 2023)
Purpose This study examined the language skills and the type and frequency of disfluencies in the spoken narrative production of typically developing Spanish-English bilingual children. Method A cross-sectional sample of 106 bilingual children (50 boys; 56 girls) enrolled in kindergarten through Grade 4, produced a total of 212 narrative retell language samples in English and Spanish. A specialized fluency coding system was implemented to index the percentage of total (%TD) and stuttering-like disfluencies (%SLD) in each language. Large-scale reference databases were used to classify children’s dual language proficiency profiles (balanced, English dominant, Spanish dominant) based on language sample analysis measures of morphosyntax and lexical diversity. Results The bilingual Spanish-English children in this study did not demonstrate significant cross-linguistic differences for mean %TD or %SLD. However, the mean %TD and %SLD in both languages exceeded the risk threshold based on monolingual English-speaking norms. English dominant bilingual children demonstrated significantly lower %TD in English than Spanish. Spanish dominant children demonstrated significantly lower %SLD in Spanish than English. Conclusions This study included the largest sample size of bilingual Spanish-English children investigated to date from a fluency perspective. The frequency of disfluencies was found to be variable across participants and change dynamically as a function of grade and dual language proficiency profiles, indicating the need for studies that employ larger sample sizes and longitudinal designs.
Keywords: Bilingual children; Disfluencies; Language sample analysis; Narratives; Stuttering; dept.cmd; peer-reviewed

The influence of side-lying position on oropharyngeal swallow function in at-risk infants: an exploratory study - Smith, Julian B.; Kamarunas, Erin; O’Donoghue, Cynthia (Clinical Pediatrics, 2023)
This investigation assessed the effect of side-lying position on infant oropharyngeal swallow physiology. Infant modified barium swallow studies (MBS) recordings were retrospectively examined in matched-pairs comparing at-risk infants swallowing in both an upright/cradled position and a side-lying position. Swallow parameters were measured independently and through a consensus coding approach. Infants fed in side-lying position showed a decrease in airway invasion severity as compared with when those same infants were fed in an upright/cradled position (P = .009). Bolus location at the time of swallow initiation was higher when infants were fed in side-lying position as compared with cradle position (P = .024), representing decreased risk of airway invasion. Infants fed in side-lying position demonstrated fewer swallows per breaths (P = .032). This pilot study validates the need for additional research to further define the mechanisms related to this improvement, and to determine how diagnosis and medical stability moderate these findings.
Keywords: dept.cmd; peer-reviewed

Interdisciplinary considerations for diagnosing aphasia in the schizoaffective patient: A case report - Warner, Heather; Cometz, Alexa (International Journal of Language & Communication Disorders, 2023)
Background Patients with schizophrenia present with both cognitive impairment as well as language difficulties. There are similarities in the language output of patients with schizophrenia and patients with aphasia, thus a differential diagnosis of patients who present with a question of dual diagnoses can be a clinical challenge. This case report highlights the importance of an interdisciplinary approach to a patient with schizophrenia who benefitted from intervention from both psychiatry and speech–language pathology services due to the patient's unique verbal output. Aims The primary aim of this case report is to highlight the critical importance of interdisciplinary collaboration in this patient population. The secondary aim is to disseminate an interesting and unique clinical phenomenon whereby the patient demonstrated an awareness of two distinct speech patterns and the unique ability to ‘code switch’ between them, something not commonly appreciated in this clinical population. Methods & Procedures This case report describes a patient seen as part of routine clinical care. Information shared was solely observational and involved dissemination of information regarding case history, assessment and treatment plan. No interventions were implemented as a part of this study. Outcomes & Results Interprofessional communication was critical in order to diagnose a patient with schizophrenia with an atypical speech pattern. The patient's language output did not manifest as a true aphasia but rather as two distinct language patterns that the patient could use at will. This ability to ‘code switch’ between languages is a unique clinical profile that is atypical of patients with schizophrenia. WHAT THIS PAPER ADDS What is already known on this subject Contemporary literature discusses the similarities between the language patterns of patients with aphasia and those with schizophrenia. There has been debate about how to classify and identify the mechanism of schizophrenic language. It is unclear whether the tangential press of speech in schizophrenia is a consequence of a formal thought disorder, or whether it constitutes an actual disorder or expressive language. Additionally, the mechanism for this speech pattern is not well defined in the literature as there is no consensus on whether it is a breakdown in linguistic processing or simply a patient's disordered thoughts being put into words. A less robust literature exists that suggests that there is a cognitive mechanism responsible for these speech patterns, as tangential speech has been linked to poor goal maintenance in other types of cognitive tasks. What this paper adds to existing knowledge This study adds an important discussion about the critical importance of interprofessional collaboration when differentially diagnosing this complex patient population. It highlights the importance of the clinical exchange of information between the two disciplines of psychiatry and speech–language pathology about a patient population where clinical information is intertwined in the way described above. Regardless of the cause of the disordered output, what is lacking in the literature is evidence of how to address the complexities of the output of these patients and how to best manage the care of the patient. This study adds a practical clinical approach to collaborating on the assessment and management of this complex patient population. Importantly, it adds a description of a clinical manifestation of the language output of a patient with schizophrenia that we do not believe to have been previously published in the literature. What are the potential or actual clinical implications of this work? Implications of this study include a much-needed shift in the field in two regards. First, to include this patient population in the groups of patients that can benefit from interprofessional collaboration for differential diagnosis and consideration for speech and language therapy. Second, it offers a practical clinical approach to inter-professional management in this patient population, something the literature is currently lacking. Additionally, publication of this unique clinical manifestation provides foundational knowledge for other clinicians appreciating similar clinical patterns of language output. To our knowledge, this is the first published case in which a patient could volitionally inhibit certain speech characteristics and thus this case study may assist in future differential diagnosis of patients with schizophrenia.
Keywords: aphasia; dept.cmd; interprofessional practice; language disorders; peer-reviewed; schizoaffective disorder